cAMP-Dependent Synaptic Plasticity at the Hippocampal Mossy Fiber Terminal - Shahoha, Meishar; Cohen, Ronni; Ben-Simon, Yoav; Ashery, Uri (Frontiers in Synaptic Neuroscience, 2022)
Cyclic adenosine monophosphate (cAMP) is a crucial second messenger involved in both pre- and postsynaptic plasticity in many neuronal types across species. In the hippocampal mossy fiber (MF) synapse, cAMP mediates presynaptic long-term potentiation and depression. The main cAMP-dependent signaling pathway linked to MF synaptic plasticity acts via the activation of the protein kinase A (PKA) molecular cascade. Accordingly, various downstream putative synaptic PKA target proteins have been linked to cAMP-dependent MF synaptic plasticity, such as synapsin, rabphilin, synaptotagmin-12, RIM1a, tomosyn, and P/Q-type calcium channels. Regulating the expression of some of these proteins alters synaptic release probability and calcium channel clustering, resulting in short- and long-term changes to synaptic efficacy. However, despite decades of research, the exact molecular mechanisms by which cAMP and PKA exert their influences in MF terminals remain largely unknown. Here, we review current knowledge of different cAMP catalysts and potential downstream PKA-dependent molecular cascades, in addition to non-canonical cAMP-dependent but PKA-independent cascades, which might serve as alternative, compensatory or competing pathways to the canonical PKA cascade. Since several other central synapses share a similar form of presynaptic plasticity with the MF, a better description of the molecular mechanisms governing MF plasticity could be key to understanding the relationship between the transcriptional and computational levels across brain regions.